PENDAMPINGAN MANAJEMEN RANTAI PASOK UNTUK PENINGKATAN DAYA SAING USAHA BATU KAPUR TUBAN - Sutrisno; Moehadi; Kharisma Laila Ismawati; Sri Wulandari (Universitas Kadiri, 2025)
Supply chain management assistance in limestone businesses aims to improve operational efficiency, managerial capacity, and market access. Limestone businesses often face challenges such as production inefficiency, high operational costs, and limited market access. Through the Supply Chain-Based Capacity Building approach, assistance is carried out through education and training related to raw material management, optimization of production processes, and more effective distribution strategies. The results of the assistance show increased production efficiency, reduced operational costs, and improvements in the business management system. In addition, business actors are better able to make data-based decisions and more structured supply chain strategies, so that business competitiveness increases. Other impacts are the expansion of market access and the implementation of more environmentally friendly business practices. Thus, this assistance contributes to the sustainability and development of a more competitive limestone business.